Influence of fermented milk permeate containing antimicrobial Lactobacillus and galactooligosaccharides on growth performance and health parameters in neonatal piglets - Badaras, Sarunas; Starkute, Vytaute; Mockus, Ernestas; Ruzauskas, Modestas; Klupsaite, Dovile; Mozuriene, Erika; Dailidaviciene, Jurgita; Dauksiene, Agila; Vadopalas, Laurynas; Bartkiene, Elena (Frontiers in Veterinary Science, 2025)
The study aimed to compare the effects of fermented milk permeate (MP) containing Pediococcus pentosaceus (MPPp) and P. acidilactici (MPPa) on growth performance, plasma parameters, and the faecal microbial, metataxonomic, and physicochemical characteristics of Topigs Norsvin Yorkshire piglets. A total of 36 1-day-old piglets were divided into three groups: (i) control group (C), (ii) MPPp group, and (iii) MPPa group. The treated groups, in addition to their full-fledged combined pre-starter diet, received 25 mL of MP daily. After the experiment, piglets in the MPPa group exhibited the highest weight gain, while piglets in the MPPp group showed the highest IgM concentration. Both experimental groups demonstrated increased Lactobacillus counts in the faeces. Although the numbers of Lactobacillus and Enterobacteria increased, these microbial changes did not show a direct correlation with growth performance. The feces of MPPa piglets had a unique volatile compound profile, characterized by higher levels of butanoic acid and indole levels, which may be linked to differences in their metataxonomic profile. The MPPp group showed a greater variety of bacterial patterns compared to the control and MPPa groups. Post-experiment, the MPPa group demonstrated the highest prevalence of specific bacterial species, Parabacteroides sp. 12,306, Terrisporobacter sp. 34,393, Holdemanella sp. 36,738, and Lachnospiraceae sp. In conclusion, feeding piglets with MPPa proved beneficial for achieving better weight gain while also promoting the proliferation of specific bacteria species and contributing to a distinctive VC profile in their faeces. These findings highlight the importance of further research into the metabolic pathways underlying these observations.